Editorial (2021)
The institutions Sociedad Colombiana de Ciencias Hortícolas (SCCH) and the Universidad Pedagógica y Tecnológica de Colombia (UPTC), editors of the journal Revista Colombiana de Ciencias Hortícolas, wish to inform our authors and readers that we will continue our efforts this year to motivate  researchers to use a broader approach so that our journal can be the most used channel for disseminating the results of their research in all areas of horticulture and for climate change and the environment in a new section of the journal. And so, we are pleased to present to our readers Volume 15 Number 1 of 2021, which includes 15 articles available in English with a digital version that uses continuous publication, i.e. accepted manuscripts are published that can subsequently  be changed with final versions.